OP0014 The Omeract-Ramris Rheumatoid Arthritis Magnetic Resonance Imaging Joint Space Narrowing Score (RAMRIS JSN) is Reproducible and Correlates Closely with Computed Tomography Assessment. (23rd January 2014) - Møller Døhn, U.; Conaghan, P. G.; Eshed, I.; Boonen, A.; Bøyesen, P.; Peterfy, C.; Lillegraven, S.; Ejbjerg, B.; Gandjbakhch, F.; Bird, P.; Foltz, V.; Genant, H.; et al.
Abstract : Background: Joint space narrowing (JSN), reflecting cartilage damage, is an important aspect of joint damage in rheumatoid arthritis (RA). A scoring system of JSN on magnetic resonance imaging (MRI) has been developed as an OMERACT initiative. However, further validation is needed before the system can be implemented in clinical trials and clinical use. Computed tomography (CT) provides optimal depiction of bone surfaces and is well suited as standard reference for assessment of JSN by MRI and X-ray. Objectives: To validate the OMERACT MRI JSN scoring system (1) for RA wrist and MCP joints by investigating its agreement with CT and X-ray, and its intrareader and interreader reliability. Methods: MRI and CT images of wrist and MCP2-5 from 14 RA patients and 1 healthy control were assessed independently twice for JSN by three readers. X-rays were scored by a single reader by the Sharp-van der Heijde method. Reliability was assessed by intraclass correlation coefficients (ICC). Images came from a clinical trial and represented a broad range of JSN on X-ray. Results: The median (range) JSN score of the assessed hand was on MRI: 13 (0-57), CT: 23 (0-58) and X-ray: 14 (0-29). MRI scores of JSN were very highly correlated with CT scores (MCP: 0.94; wrist: 0.92; MCP+wrist: 0.92). X-ray JSN scores correlated with MRI and CT (MCP2-5: 0.49 and 0.56; wrist: 0.55 and 0.43), see table. On MRI and CT, high intraobserver (ICCs≥0.91 and ≥0.75, respectively) and interobserver (ICCs≥0.82 and ≥0.66, respectively) reliability was observed. In general, lower agreement was found in MCP joints compared to the wrist. Conclusions: The OMERACT-RAMRIS MRI JSN scoring system showed very high agreement with CT assessment, whereas X-ray scores were moderately correlated. Both MRI and CT scores showed a high intra- and interreader reliability. The MRI JSN score may, after further validation, become a useful tool in RA clinical trials. References: Østergaard M, et al.: Development and preliminary validation of a magnetic resonance imaging joint space narrowing score for use in rheumatoid arthritis: potential adjunct to the OMERACT RA MRI scoring system. J Rheumatol. 2011;38:2045-50. Disclosure of Interest: None Declared